Proceso de atención de enfermería en neonato con síndrome de abstinencia. - Franco Vargas, Karla Karina (2023)
Neonatal abstinence syndrome is the main manifestation in the newborn that appears after drug consumption (Heroin) during pregnancy. Internationally, around 246 million people are affected, that is, 1 in every 20 people between the ages of 15 and 64. The prevalence in Ecuador increases by 5%; during the gestation period, childbirth and postpartum. Today it is known that in the provinces of Guayas and Santa Elena its increase is alarming, according to the SETED (secretariat for comprehensive drug prevention) 2 out of every 3 cities in the coastal region consume more drugs, the highest prevalence is found in: Santa Elena with 5.7%, Durán 4.0%, Guayaquil 8.80% and La Libertad 7.30%. In the present clinical case study, a neonatal patient with a diagnosis of withdrawal syndrome was shown at the University Hospital of Guayaquil, who presented alarm signs such as vomiting, diarrhea, hyperacusis, tachypnea (60 breaths per minute), and tachycardia (182 beats per minute), added to this, there was an alteration in the toxicological tests (positive for opioids), and the findings found in the physical examination (paleness and dehydration). All functional patterns were evaluated, obtaining 4 affected patterns ( elimination and exchange pattern, activity and rest pattern, perceptual cognitive pattern, role-relations pattern) that required prioritized attention in terms of nursing care (fluid management, hyperthermia management and emotional support). After the establishment and application of the nursing care process, a follow-up was carried out, obtaining scores (+2 and +3 on the Likert scale), strict control of their vital signs, and alarm signs (condition and integrity). of skin, membrane and mucous membranes) (hemodynamic status) (neurological reactions to external stimuli), in order to continually evaluate neonatal well-being until the improvement in their health status is confirmed. These nursing activities were carried out throughout the entire hospitalization with the aim of safeguarding the patient's safety and avoiding dangerous states. On her last day, she was discharged by the treating physician who, based on laboratory tests, monitoring of vital signs and completion of pharmacological treatment, provided education to the parent about the consequences of continuing under the influence of opiates, in addition to the staff. Nursing provides emotional and psychological support to avoid such consumption of psychotropic substances and thus avoid new hospitalizations.